Experimental Study and Low Temperature Friction Characteristic of Angular Contact Ball Bearing - Qiu Shengdong (Jixie chuandong)
In order to analyze the low temperature friction characteristics of angular contact ball bearings.Firstly,the change of low temperature structure of bearing is analyzed by finite element software,the changes of the low temperature structure,the change of the clearance and the change of the contact angle of the bearing are simulated and analyzed. The decrease of temperature will make the clearance of bearing larger and the contact angle larger. The change of temperature on the viscosity of grease is analyzed. Then the friction torque calculation model of the existing bearing is cited,and the friction torque of the bearing is calculated with the change of speed,preload,the radius of curvature and the temperature of the inner ring. Analysis of the trend of bearing friction torque under low temperature,dynamic pressure bearing friction torque for the friction torque of the80% fluid bearing at low temperature,low temperature and friction properties of lubricating grease viscosity coefficient of bearing the greatest impact,under the condition of low temperature bearing due to friction torque caused by the decrease of elastic hysteresis. Finally,the friction torque of bearing is tested by experimental method,and the result is compared with the simulation result. The error is less than 12%,which proves the accuracy of the calculation and provides a theoretical basis for the use of bearings at low temperature.